2022
DOI: 10.1002/jmv.28223
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and clinical significance of plasma IL‐18, sCD14, and sCD163 levels in patients with HIV‐1 infection

Abstract: Biomarkers of monocyte‐macrophages activation and inflammation in plasma such as interleukin‐18 (IL‐18), soluble leukocyte differentiation antigen 14 (sCD14), and sCD163 are associated with disease severity and prognosis in HIV‐1 infected patients, however, their relationships with efficacy of antiretroviral therapy (ART) need further investigation. We aimed to characterize and explore the clinical significance of plasma IL‐18, sCD14, and sCD163 in this population. This was a retrospective cohort study consist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…One possible explanation is that long-term virological response may be less affected by baseline viral load and baseline immune function than short-term (48 week) virological responses. This was supported by our previous work showing that lower baseline HIV-1 RNA levels could independently predict higher rates of virological responses at week 48 of ART ( 7 ). In addition, the predictive effectiveness of week 24 IL-18 on long-term virological response is extremely strong, and when they are simultaneously included in the multivariate model, the predictive effectiveness of baseline HIV-1 RNA and baseline CD4+ cell count may appear to be very weak, which is not uncommon in multivariate analysis.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…One possible explanation is that long-term virological response may be less affected by baseline viral load and baseline immune function than short-term (48 week) virological responses. This was supported by our previous work showing that lower baseline HIV-1 RNA levels could independently predict higher rates of virological responses at week 48 of ART ( 7 ). In addition, the predictive effectiveness of week 24 IL-18 on long-term virological response is extremely strong, and when they are simultaneously included in the multivariate model, the predictive effectiveness of baseline HIV-1 RNA and baseline CD4+ cell count may appear to be very weak, which is not uncommon in multivariate analysis.…”
Section: Discussionsupporting
confidence: 76%
“…Numerous studies have revealed that chronic immune inflammation is a hallmark of HIV-1 infection that persists even after several years of successful ART and is associated with noninfectious complications of HIV-1, including cardiovascular disease, non-AIDS malignancies and frailty ( 10 , 11 ). Our recent short-term study demonstrated that plasma IL-18 decreased after initiation of ART up to 24 weeks but rebounded by 48 weeks post-ART initiation ( 7 ). The current study further uncovered the long-term dynamic changes in IL-18, that is, it continued to rise after 48 weeks of ART.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…IL-18 (interleukin-18) is a proinflammatory cytokine involved in the regulation of the immune response and inflammation [51][52][53]. Increased IL-18 levels have been observed in patients with HIV and pneumonia, suggesting an exacerbated inflammatory response [51,54,55]. IP10 (interferon gamma-inducible protein 10), also known as CXCL10, is a chemoattractive cytokine that attracts inflammatory cells, especially T lymphocytes, to the site of infection [56,57].…”
Section: Discussionmentioning
confidence: 99%